Therapeutic advances propelled by deciphering tumor biology and immunology-highlights of the 8th Heidelberg Myeloma Workshop - Lutz, Raphael; Friedrich, Mirco; Raab, Marc-Steffen; Weinhold, Niels; Goldschmidt, Hartmut (Cancers, 2021)
Simple Summary The 8th Heidelberg Myeloma Workshop was held on 16-17 April 2021 at the University Hospital Heidelberg, Germany. The main topics of the meeting were diagnostics and prognostic factors of early-phase multiple myeloma (MM), the role of immunotherapy, as well as the biology and genomics of MM. This manuscript reports on recent advances in MM research and points out future directions. The diagnostics and treatment of newly diagnosed and relapsed MM are continuously evolving. While advances in the field of (single cell) genetic analysis now allow for characterization of the disease at an unprecedented resolution, immunotherapeutic approaches and MRD testing are at the forefront of the current clinical trial landscape. Here, we discuss research progress aimed at gaining a better understanding of this heterogenous disease entity, presented at the 8th Heidelberg Myeloma Workshop. We address the questions of whether biology can guide treatment decisions in MM and how assessment for measurable residual disease can help physicians in clinical decision-making. Finally, we summarize current developments in immunotherapeutic approaches that promise improved patient outcomes for MM patients. Besides summarizing key developments in MM research, we highlight perspectives given by key opinion leaders in the field.
Gesehen am 11.10.2021